Business Innovation in the Spanish Companies (2003-2016): The Human Factors Definitively Count - Fernando Fernández-Bonilla; Julio Navío-Marco; Covadonga Gijón (International Telecommunications Society (ITS), 2021)
This research analyses determining factors of business innovation in Spain during a long period of study. A panel is carried out with data from 2003 to 2016 obtained from the Spanish Technological Innovation Panel (PITEC) survey to determine their influence, and in particular variables related to human factors are included to observe their impact on innovation. Along with other general factors such as firm size, ownership of the company, turnover and financing of the company, it is found that training in R & D & I has a relevant influence on business innovation. The article put special emphasis on human factors and is an invitation to continue their study.
Keywords: 330; business innovation; panel data; RDI